Subcutaneous lipomas: A minimally invasive method for resection of subcutaneous lipomas preserving retaining ligaments - Sakamoto, Akio (Eur J Plast Surg, 2017)
BACKGROUND: Lipomas are common benign tumors usually located in the subcutaneous tissues. Resection of lipomas frequently requires incisions equal to the diameter of the tumor. The “squeeze technique” with a small incision is well-described, but is frequently not successful, particularly for lipomas in the shoulder region. We report a method for resection of subcutaneous lipomas that preserves retaining ligaments. METHODS: Lipomas are characterized by high signal intensity on T1- and T2-weighted images on magnetic resonance imaging. Retaining ligaments demonstrate low signal intensity on T1-weighted images and high signal intensity on T2-weighted images with fat-suppression. Through a 1 in. incision, lipomas were detached from the retaining ligaments bluntly with a finger. Tumors were then extracted either in a piecemeal fashion or with the “squeeze technique.” Complete lipoma resection was visually confirmed through the incisions. For the current report, we analyzed 18 large lipomas resected by this method, with “large” defined as equal to or greater than 5 cm in diameter. RESULTS: The 18 patients included four males and 14 females with a mean age of 53.4 (26–72). The mean lipoma size was 6.6 cm (5–12). Locations included the shoulder in nine cases (50%), the upper arm in five cases (28%), the back in two cases (11%), and the thigh in two cases (11%). Retaining ligaments were identified by MRI in all cases. Lipomas were located between retaining ligaments at the periphery of the tumor. All three lipomas larger than 10 cm were located in the shoulder. There was no difference in the technical difficulty of resection of these compared with lipomas less than 10 cm in diameter. There were no cases of chronic pain or residual hypoesthesia at the incision sites. CONCLUSIONS: The method is an easy and minimally invasive way to achieve complete resection, even for large lipomas, regardless of anatomical location. The method may contribute to reduction of side effects including residual hypoesthesia and chronic pain at the incision site, due to the small incision and preservation of retaining ligaments, which may contain cutaneous nerves. Level of Evidence: Level IV, therapeutic study.